The Effect of Dongklak Dance on the Gross Motor Skills of Children Aged 5–6 Years - Rahayu, Apriliya; Maulidiyah, Eka Cahya (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Gross motor development is a crucial aspect of early childhood growth. One method that can be used to improve gross motor skills is through dance activities, particularly the Dongklak Dance. This study aims to determine the effect of Dongklak Dance on the gross motor development of children aged 5–6 years. This research employed a quantitative method using a pre-experimental one-group pretest–posttest design. The research subjects consisted of 14 children aged 5–6 years, selected through purposive sampling. Data were collected through observation and gross motor skills tests, analyzed using the Wilcoxon test. The Wilcoxon test produced a p-value < 0.05, showing improvements in balance, coordination, and agility after the Dongklak Dance treatment. In conclusion, the Dongklak Dance can be used as an effective method to enhance gross motor skills in early childhood.